Investigating the Effect of Warm-up Exercises FIFA 11+ on Injury Prevention for Football Athletes: A Narrative Review - Arzani, Parisa; Mikaili, Saeed (Journal of Clinical Physiotherapy Research, 2021)
Introduction: Football is one of the most popular sports in the world, however, the risk of injury in football players is high. So, it is necessary to do exercises that prevent injury. The FIFA 11+ warm-up program is one of the most recent injury prevention programs developed by FIFA. This program includes warm-up preparation exercises. Recently, many studies have been conducted on the effectiveness of this program in injury prevention. The purpose of this review study was to investigate the effect of FIFA 11+ training on the extent to which football players are injured and their performance. Methods and Materials: Using the keywords of Football, Soccer, Injury prevention, FIFA 11, and FIFA 11+ in the Google Scholar, Science Direct, and PubMed databases, related studies were searched from 2002 to 2019. Finally, 6 studies had the inclusion criteria. Results: Players who used the FIFA 11+ program reported less damage. Also, those who followed the intermittent exercise program showed a significant improvement in performance and health-related factors. Conclusion: FIFA 11+ training is recommended as a type of warm-up exercise due to its ease of use in soccer athletes, as it has been shown that doing this exercise program can significantly reduce the risk of injury in footballers.